Thinking critically about ethical issues - Ruggiero, Vincent Ryan (McGraw-Hill Higher Education, 2008)
This concise, accessible text emphasizes doing ethical analysis and thinking critically about ethical issues, rather than focusing on ethical theory or the history of ethics. Ruggiero's readers are invited to apply ethical principles to issues that exemplify the kinds of moral challenges encountered in everyday life. It engages students' minds, stimulates enthusiasm, and makes teaching more effective and rewarding.